The Temperature dependence of active and reactive impedances of PMMA-EC-LiTf / MgTf2 solid polymer electrolytes: Temperature dependence of active and reactive impedances of PMMA-EC-LiTf / MgTf2 solid polymer electrolytes - uktamaliyev, bekzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In this work, PMMA-EC-LiTf, PMMA-EC-MgTf2 samples were prepared at a concentration of 20%. Using Nyquist coordinates, results were obtained for active and reactive impedances at temperatures from 243K to 283 K and at temperatures from 303 K to 373 K. Rb from MgTf2 system are lower than LiTf in the room temperature. PMMA-EC-MgTf2 sample conductivity is , PMMA-EC-LiTf2 sample conductivity is